Effect of discarded smooth and rough glass waste on mechanical properties of cement concrete - S V, Sivapriya; M. J., Hariraj; T., Rajarajan; Kumar. S, Vishnu (Revista de la Construcción. Journal of Construction, 2024)
The depletion of natural material leads to an alternative material in its place in concrete. If the alternative material is a recycled material, it serves the purpose of reuse and reduces its impact on the environment. One such material is glass waste. In this study, two varied textures of transparent waste glass of size 12.5 mm are used as an alternative material for coarse aggregate with 10, 20, and 30% of replacement. The mechanical properties such as compressive strength, flexural strength and split tensile strength are studied along with water absorption and unit weight characteristics. It is observed that the compressive strength showed a maximum value at 10% replacement for both textured glasses, beyond that it reduces irrespective of curing period. A similar trend is observed in flexural strength also. The split tensile strength increases with percentage replacement due to the contribution of waste glass in interface transmission zone. The water absorption falls well within 3% for all the combinations indicating its good behaviour. The unit weight decreases making it suitable for making lighter material. When comparing cost, there is a reduction in cost by 3 to 7 %; however, it is minimum it addresses the environmental aspects.